Dialektika Positivisme dan Epistemologi Islam: Mencari Paradigma Integratif dalam Pendidikan - Anjali Sriwijbant; Tejo Waskito (SITASI: Journal of Islamic Studies and Inclusive Education, 2026)
This article discusses the relevance and problems of Auguste Comte’s positivist thought in the context of Islamic education. Positivism, as a scientific paradigm, emphasizes objectivity, empiricism, and rationality as the sole sources of truth. This paradigm has greatly influenced the modern education system, which tends to neglect moral and spiritual dimensions. From the perspective of Islamic education, the positivist approach is considered reductionistic because it denies revelation and transcendental values as integral sources of knowledge. This study employs a qualitative method through a literature review to elaborate on the essence of positivism, the epistemological critique from Islam, and an integrative framework for the development of Islamic educational knowledge. The findings indicate the necessity of repositioning the epistemology of Islamic education toward a post-positivist model that unites revelation, reason, and empirical experience within a unified tauhid (monotheistic) system of knowledge.